Inside Back Cover: A Prototype of a Volumetric Three‐Dimensional Display Based on Programmable Photo‐Activated Phosphorescence (Angew. Chem. Int. Ed. 22/2020). Issue 22 (15th April 2020) - Wan, Shigang; Zhou, Hongqi; Lin, Jinxiong; Lu, Wei
Abstract : A volumetric 3D display system was developed by harnessing the photo‐activated phosphorescence of two selected molecular phosphors in a photochemically deoxygenating solvent, as reported by W. Lu and co‐workers in their Communication on page 8416 . The phosphorescent voxels, 3D images, and animations are well‐defined by the intersections of two programmable excitation beams, and are convenient for visualization with the naked eye with relatively high resolution.